Self-Efficacy of Women Prisoners Who Are Infected By HIV - Mitro Subroto; Ade Cici Rohayati (GoAcademica Research & Publishing, 2020)
The problem is the number of cases of Prisoners/Detainees contracting/infected with HIV/AIDS in correctional institutions/detention in Indonesia and based on data on female prisoners in Semester II (June-November) in 2019, on average each month 1,112 people, of which 12% were female prisoners infected with HIV, as well as looking at the mental and psychological vulnerability of female prisoners, the authors are interested in researching about female prisoners infected with HIV. In this study, the authors examined the self-efficacy of female prisoners infected with HIV/AIDS and the role of prison officers in motivating and increasing prisoners' self-efficacy. The study was conducted using a comparative qualitative method that is conducting research at 2 (two) different loci to compare the results of each locus. The informants of the study selected 13 (thirteen) female prisoners infected with HIV, 2 (two) prison doctors and 2 (two) heads of the sub-section of Bimkemaswat. The study uses self-efficacy theory which has 4 (four) processes in the formation of self-efficacy and 4 (four) components of self-efficacy improvement. The process and components are used as a guide in interviewing informants. The results of the study, there are differences in the self-efficacy of prisoners at each locus, due to differences in treatment and social support that can increase the self-efficacy of prisoners. Based on the results of the analysis concluded that the self-efficacy of HIV-infected female prisoners in LPP Tangerang is better than female prisoners infected with HIV in LPP Jakarta.